Study on the development of motor skills in students through badminton - Tănasă Ionuț Bogdan; Vizitiu Elena (Editura Univeristatii "Stefan cel Mare" din Suceava, 2022)
The development of students' motor skills has been a permanent concern of physical education and sport specialists, and has been continuously optimised over the years. In the proposed study we started from the premise that by applying the specific means of badminton game to the experimental class, the level of motor skills development can increase compared to the control class. The study was carried out at the "Al. I. Cuza " in Fălticeni, Suceava town, in the period September-December 2022. The students participating in the study were from classes a- V, both girls and boys. The aim of the research is to select the most effective means of badminton to develop the motor skills of the students under study in physical education and sports lessons. In secondary school students, the exercises specific to the game of badminton and the game itself allow the development of their motor and mental skills.